THE SERVICE AND EDUCATIONAL MISSION OF THE CHURCH IN MODERN SOCIETY AS A FACTOR OF FORMING THE FUNDAMENTALS OF THE SOCIAL IDEAL - Anatoliy Kysliy ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The Church, having a rich experience of work in the social environment, tries not only to serve humanity, realizing its vocation, but also to fulfill the educational mission, which is unique in meaning, content and forms of expression. The gradual development of modern theological thought and religious philosophy is influenced by the understanding of the Church's involvement in the current priorities of social life as a certain spiritual and moral arbiter. The complexity of the question of the influence of Christianity on the formation of the value bases of the social ideal lies in the confessional features of the positioning of churches in a globalized world.